Consumption of energy drinks by children and young people: a rapid review examining evidence of physical effects and consumer attitudes. Issue 10 (8th October 2016) - Visram, Shelina; Cheetham, Mandy; Riby, Deborah M; Crossley, Stephen J; Lake, Amelia A
Abstract : Objective: To examine patterns of energy drink consumption by children and young people, attitudes towards these drinks, and any associations with health or other outcomes. Design: Rapid evidence assessment and narrative synthesis. Data sources: 9 electronic bibliographic databases, reference lists of relevant studies and searches of the internet. Results: A total of 410 studies were located, with 46 meeting the inclusion criteria. The majority employed a cross-sectional design, involved participants aged 11–18 years, and were conducted in North America or Europe. Consumption of energy drinks by children and young people was found to be patterned by gender, with boys consuming more than girls, and also by activity levels, with the highest consumption observed in the most and least sedentary individuals. Several studies identified a strong, positive association between the use of energy drinks and higher odds of health-damaging behaviours, as well as physical health symptoms such as headaches, stomach aches, hyperactivity and insomnia. There was some evidence of a dose–response effect. 2 experimental studies involving small numbers of junior athletes demonstrated a positive impact on limited aspects of sports performance. 3 themes emerged from the qualitative studies: reasons for use; influences on use; and perceived efficacy and impact. Taste and energy-seeking were identified as key drivers, and branding and marketing were highlighted as major influences on young people's consumption choices. Awareness of possible negative effects was low. Conclusions: There is growing evidence that consumption of energy drinks is associated with a range of adverse outcomes and risk behaviours in terms of children's health and well-being. However, taste, brand loyalty and perceived positive effects combine to ensure their popularity with young consumers. More research is needed to explore the short-term and long-term impacts in all spheres, including health, behaviour and education. Trial registration number: CRD42014010192.